Effect of torso reflections from simplified torso models on head-related transfer function simulation and ipsilateral perception of elevation. (December 2022) - Lan, Yu; Yin, Tingwei; Yu, Guangzheng
Highlights: The torso reflections in head-related transfer functions (HRTFs) of various simplified model were compared and analyzed. To further evaluate the effect of torso reflections, we conducted the psychoacoustic experiment. The human-like torso shape can provide enough torso reflection, improving low-frequency lateral elevation localization performance. Abstract: The effect of torso reflection on head-related transfer functions (HRTFs) is considered a suitable elevation localization cue for lateral sound sources below 3.0 kHz, and various torso models have been hitherto adopted in HRTF simulation. However, their torso reflection effects have not been compared in detail. This work analyzes the torso reflection effects of the representative torso models on HRTFs, and further evaluates their elevation localization performance via psychoacoustic experiments. The results show that the semi-ellipsoidal torso and truncated Knowles Electronics Mannequin for Acoustic Research (KEMAR) torso, both of which have considerable advantages over the spherical torso, can achieve better elevation localization performance, which validates the torso with human-like shape provide enough torso reflection and have a better ability in low-frequency lateral elevation perception.